Comparison of fracture resistance between two monolithic and one veneered zirconia materials on molar crowns after thermomechanical fatigue - Kayalı, Faisal (My University, 2019)
Amacı: Bu in vitro çalışmanın amacı, iki farklı monolitik zirkonya materyali ve bir zirkonya altyapı materyali kullanılarak üretilen tek üye kronların, termomekanik yaşlandırma sonrası kırılma direncini değerlendirmektir.Gereç ve yöntemler: 72 adet çekilmiş molar diş toplandı ve preparasyonları yapıldı. Örnekler, kullanılan zirkonya materyaline göre, üç gruba (n = 24) ayrılacaktır. 1. grupta GC Initial (monolitik), 2. grupta Dentsply Sirona TZI (monolitik) ve grupta Dentsply Sirona ZI (veneered) materyalleri kullandı. Peparasyonarı takiben tüm dişler Sirona inEos X5 kullanılarak tarandı. Zirkonya kuronlar, Cerec inLab MC X5 sistemi tarafından tasarlanıp üretiledi. Kronlar G-CEM LinkAce self adeziv siman kullanılarak simante edildi. Her bir gruptaki simante edilmiş haldeki kuronların on iki tanesine çiğneme simülatörü (SD Mechatronic CS-4) kullanılarak termomekanik yaşlandırma yapıldı. Tüm örneklere Universal test makinesi (Shimadzu AGS-X) kullanılarak kırılma dayanımları ölçülecek ve karşılaştırdı. Elde edilen veriler SPSS 23.00 paket program kullanılarak istatistik olarak değerlendirdi.Bulgular: Kontrol grubunun kırılma dayanımı değerleri TMF grubuna göre istatistiksel olarak anlamlı derecede yüksek bulunmuştur. GC ve TZI grupları arasında kırılma dayanımı açısından anlamlı fark tespit edilememiştir.Sonuç: Çalışmamız termomekanik yordunluğun kırılma dayanımı üzerinde anlamlı ve belirgin bir etkisinin olduğunu göstermiştir.

Aim: The purpose of this in-vitro study is to evaluate fracture resistance of two monolithic and one veneered zirconia crowns on human molar teeth fabricated after thermomechanical fatigue.Materials and methods: Seventy-two human molar teeth were prepared to receive zirconia crowns. The specimens were divided into three experimental groups (n=24) according to restoration design, monolithic or veneered. The crowns were fabricated from GC initial zirconia, Dentsply Sirona TZI and Dentsply Sirona ZI. The prepared teeth were scanned with Sirona inEos X5 and milled with Cerec inLab MC X5. The crowns of each group were cemented to prepared teeth using resin cement. Twelve crowns of each experimental group underwent thermomechanical fatigue (TMF) using chewing Simulator (SD Mechatronik CS-4) for 240 000 chewing cycles with load of (100 N) and thermocycling (5 °C/ 55 °C), the remaining 12 crowns in each group did not undergo any thermomechanical fatigue and were considered as control group. All specimens were loaded until fracture using universal testing machine (Shimadzu AGS-X). Forces were applied from occlusal surface with 90o angle. Loads of fracture were recorded. Collected data of fracture loads of all specimens were analyzed using SPSS 23.00 program.Findings: Although thermomechanical fatigue significantly decreased fracture loads of only monolithic groups, monolithic zirconia crowns had higher fracture loads than veneered one.Conclusion: Thermomechanical fatigue has significant influence on monolithic zirconia, however, it showed higher fracture loads and can be alternative to veneered design.
Keywords: Diş; fracture; Health; kırılma; monolithic; monolitik; Sağlık; termomekanik yaşlandırma; thermomechanical fatigue; Tooth; zirconia; zirkonia